Achieving supply chain 'Leagility' through a project management orientation. Issue 1 (2nd January 2016) - Gaudenzi, Barbara; Christopher, Martin
Abstract : Many forces have combined to make today's supply chains more complex than ever before. These forces include the significant trend to out-sourcing; the growth of offshore manufacturing and procurement; the rising demand for customer-specific solutions and the globalisation of markets. The paper highlights the challenges that organisations must address in order to gain and retain competitiveness in today's markets – in particular, the need to achieve ever lower costs while simultaneously enhancing responsiveness. In other words, the need is to develop hybrid supply chains that are both 'lean' and 'agile'. Using a single case study of a global telecommunications company as an example, the authors demonstrate how supply chain complexity can effectively be mastered by adopting a project management orientation and in the process enabling outcomes that are 'leagile', that is, both lean and agile.